THE ROLE OF WOMEN IN THE SYRIAN NATIONAL MOVEMENT (1880–1967) - Sabah Algam Musa (Scholars Digest Publishing, 2025)
This study examines the historical role of Syrian women in the national movement from 1880 to 1967, highlighting their active participation in political, social, and cultural spheres. During the Ottoman period, reforms in education and the rise of private and missionary schools enhanced women’s access to learning, while feminist journalism and the establishment of early associations reflected growing awareness of women’s rights. Under the French Mandate, Syrian women played a critical role in resistance movements such as the Great Syrian Revolution (1925–1927) and the general strike of 1936, offering logistical, financial, and direct support to the national struggle. They also advanced the establishment of associations that demanded reforms in education, personal status laws, and political rights. Following independence in 1946, women engaged more directly in political life, seeking parliamentary representation, legal reforms, and integration into political parties including the Communist, National, and Ba’ath parties. Despite setbacks caused by successive military coups, women achieved the right to vote and later to run for office, marking a turning point in their political empowerment. The research emphasizes that Syrian women’s contributions were not limited to auxiliary roles but extended to leadership, advocacy, and activism that shaped the trajectory of national politics and social change. By analyzing their participation across three historical phases—Ottoman rule, the French Mandate, and independence—this study demonstrates the evolution of women’s roles from marginalization to active citizenship, underscoring their enduring influence in the pursuit of equality, independence, and national identity.
Keywords: Syrian women, national movement, Ottoman reforms, French Mandate, political empowerment.